The administrative process and organizational effectiveness - Alibin, Perfecto A.
This study investigated the influence of the different types of decision making and the components of administrative process categorized as (1) programming, (2) coordinating, and (3) evaluating on the effectiveness of 6 state and 15 private colleges and universities in the National Capital Region. School effectiveness in terms of performance in the Certified Public Accountant board examination, holding power in education and commerce/business administration, employee satisfaction, and number of research outputs were examined based on data gathered from 74 school administrators and 286 faculty and administrative personnel. Individual programming, compromise decision-making and peer evaluation are significantly related to performance in board examinations, the first two inversely and the last positively. Management evaluation and routine decision making are negatively related to employee satisfaction while heuristic decision making in coordinating and evaluating is positively related to employee satisfaction and research. Compromise decision making in evaluating is inversely related to research.